Polyester composition as well as preparation method and application thereof
By introducing polysulfone and talc powder into the traditional bromine flame retardant system polyester for compounding, a polyester composition was prepared, which solved the problem of poor flame retardant performance of extremely thin flame retardant polyester materials during combustion, and achieved green and environmentally friendly and efficient flame retardant effects.
Patent Information
- Application Number
- CN202411994590.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to improve the flame retardant performance of extremely thin flame retardant polyester materials during combustion without using fluorine-containing substances, especially in thin-wall designs.
By introducing polysulfone and talc powder into the traditional bromine flame retardant system polyester for compounding, a polyester composition was prepared, which avoided the use of fluorine-containing substances and achieved excellent thin-wall flame retardant effect.
Without using PFAS-type substances, the polyester composition can achieve 0.8mm V-0 flame retardant, and in some preferred technical solutions, it can achieve 0.4mm ultra-thin V-0 flame retardant, meeting the application needs of green and environmentally friendly and efficient flame retardant.
Smart Images

Figure BDA0005224320170000101 
Figure BDA0005224320170000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a polyester composition and a preparation method and application thereof. Background Art
[0002] Polybutylene terephthalate (PBT) is a milky white, translucent, crystalline thermoplastic resin with a heat deformation temperature of over 180°C. It can be used for a long time at 140°C. It has a high surface gloss, a fast crystallization rate, good fluidity, excellent formability, good thermal stability, and especially low thermal expansion and dimensional shrinkage. It has strong chemical resistance, good solvent resistance, good weather resistance, high dielectric strength, good electrical properties, low hygroscopicity, and minimal effect on electrical and dimensional stability.
[0003] Polyethylene terephthalate (PET) is a milky white or light yellow highly crystalline polymer with a highly symmetrical molecular structure and a certain crystal orientation ability. It has excellent weather resistance, creep resistance, fatigue resistance, low wear and high hardness. It is the toughest material among thermoplastics. Its alloy resin has a wide range of applications and can replace high-gloss materials such as ABS and other electrical-resistant, heat-resistant and light-resistant functional parts.
[0004] Both PBT and PET have excellent mechanical properties and processing properties. They are widely used polymer polyester materials and play an important role in the fields of automobiles, electronics, and home appliances.
[0005] With the development of modern high technology, more and more products are designed with thin walls. In order to reduce the flame retardant thickness of the traditional bromine antimony flame retardant system, it is often necessary to add polytetrafluoroethylene (PTFE) as an anti-drip agent. For example, CN113248881A discloses a high-performance PET / PBT material for an air-conditioning compressor junction box, which comprises, by weight: 35-55 parts of PET, 0-8 parts of PBT, 30 parts of glass fiber, 3-10 parts of EMA, 5-15 parts of decabromodiphenylethane, 2-5 parts of antimony trioxide, 0.1-0.5 parts of polytetrafluoroethylene, 1-5 parts of E / MAA, 0.1-0.5 parts of HK-185P nucleating agent, 0.1-0.5 parts of talc, 0.1-0.5 parts of nucleating accelerator, 0.1-0.5 parts of ester exchange inhibitor, 0.1-0.3 parts of light stabilizer, 0.1-0.3 parts of ultraviolet absorber, 0.2-0.8 parts of lubricant, 0.1-0.3 parts of antioxidant A, and auxiliary antioxidant B. 0.1-0.3 parts, coupling agent 0.1-0.4 parts, can solve the problems of poor temperature resistance, rigidity, impact resistance and high product scrap rate of PET materials.
[0006] However, as people's safety awareness increases, the pollution problem of per- and polyfluoroalkyl substances (PFAS) has attracted more and more global attention, and many European and American countries have introduced new regulations to restrict the use of PFAS. As a polymerized polyfluoroalkyl substance, PTFE has also attracted more and more attention. But so far, there is no obvious technical means to replace PTFE to suppress the dripping problem of extremely thin flame-retardant polyester materials during combustion.
[0007] Therefore, how to improve the flame retardant properties of thin-walled materials without using fluorine-containing substances has become an urgent problem to be solved. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a polyester composition and a preparation method and application thereof, by introducing polysulfone and talcum powder into the traditional bromide-based flame retardant polyester for compounding, thereby achieving excellent thin-wall flame retardant effect, avoiding the use of fluorine-containing substances, and eliminating people's concerns about the use of PFAS in materials.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a polyester composition, which comprises, by weight, 40-60 parts of polyester resin, 5-20 parts of brominated flame retardant, 0.5-5 parts of synergistic flame retardant, 0.1-15 parts of polysulfone, 0.05-5 parts of talc, and 15-40 parts of reinforcing material;
[0011] The polyester composition does not include PFAS substances.
[0012] Among them, PFAS substances (perfluoroalkyl substances and polyfluoroalkyl substances) refer to organic fluorine compounds containing at least one fully fluorinated carbon atom (-CF2- or -CF3 group).
[0013] The fluorine content in the polyester composition is ≤100 ppm (for example, it may be 2 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm or 100 ppm, etc.), and preferably the fluorine content in the polyester composition is ≤25 ppm.
[0014] In the prior art, when a brominated flame retardant is used to prepare a polyester composition, PFAS substances (such as fluorinated anti-drip agents, PTFE) are often used to improve the flame retardant properties of the polyester composition. However, the use of PFAS substances will result in an excessively high fluorine content in the polyester composition, which does not meet application requirements. The present invention designs the composition of the polyester composition and prepares a polyester composition with excellent flame retardant properties through the coordination of various components without using PFAS substances.
[0015] The polyester composition provided by the present invention uses polyester resin as a base material, and is compounded with polysulfone, talcum powder and a bromine-based flame retardant system to inhibit the dripping of an extremely thin flame-retardant polyester material during combustion, and synergistically improve the flame retardant performance of the material under thin walls. The composition contains no fluorine-containing substances, and takes into account the application requirements of both green environmental protection and high flame retardant performance of polyester materials. The polyester resin is 40-60 parts, for example, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts.
[0016] The amount of the brominated flame retardant is 5-20 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts or 18 parts.
[0017] The synergistic flame retardant is 0.5-5 parts, for example, 0.8 parts, 1 part, 1.5 parts, 2 parts, 3 parts or 4 parts.
[0018] The polysulfone is 0.1-15 parts, for example, 0.5 parts, 1 parts, 2 parts, 3 parts, 5 parts, 8 parts, 10 parts or 12 parts.
[0019] The talc powder is 0.05-5 parts, for example, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 3 parts or 4 parts.
[0020] The reinforcement material may be 15-40 parts, for example, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 27 parts, 30 parts, 33 parts, 36 parts, 38 parts or 40 parts.
[0021] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.
[0022] Preferably, the polyester composition comprises, by weight, 45-55 parts of polyester resin (for example, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts or 55 parts), 8-15 parts of brominated flame retardant (for example, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts), 1-4 parts of synergistic flame retardant (for example, 1.5 parts, 2 parts, 2.5 parts, 3 parts or 3.5 parts, etc.), polysulfone 0.5-5 parts (for example, it can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts or 4 parts, etc.), talc powder 0.3-3 parts (for example, it can be 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts or 2.5 parts, etc.), reinforcing material 15-40 parts (for example, it can be 15 parts, 18 parts, 20 parts, 25 parts, 30 parts, 38 parts or 40 parts, etc.).
[0023] As a preferred technical solution of the present invention, the mass fraction of the polyester resin in the polyester composition is 40-65%, for example, it can be 40%, 45%, 50%, 55%, 60% or 65%.
[0024] As a preferred technical solution of the present invention, the mass fraction of the brominated flame retardant in the polyester composition is 5-20%, for example, 5%, 7%, 10%, 12%, 15%, 18% or 20%.
[0025] As a preferred technical solution of the present invention, the mass fraction of the synergistic flame retardant in the polyester composition is 0.5-5%, for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0026] As a preferred technical solution of the present invention, the mass fraction of polysulfone in the polyester composition is 0.2-4%, for example, it can be 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%.
[0027] As a preferred technical solution of the present invention, the mass fraction of talc in the polyester composition is 0.1-4%, for example, it can be 0.1%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3% or 3.5%.
[0028] As a preferred technical solution of the present invention, the mass fraction of the reinforcing material in the polyester composition is 20-35%, for example, it can be 20%, 22%, 25%, 27%, 30%, 33% or 35%.
[0029] Preferably, the mass ratio of the polysulfone to talc is (1-10):1, wherein the specific value of (1-10) can be, for example, 1.5, 2, 2.5, 3, 3.5, 4, 5, 6, 7, 8 or 9.
[0030] Preferably, the polyester resin includes polybutylene terephthalate resin and / or polyethylene terephthalate.
[0031] Preferably, the polybutylene terephthalate resin includes a homopolymeric polybutylene terephthalate resin or a copolymer containing a polybutylene terephthalate unit.
[0032] The polybutylene terephthalate resin (PBT) resin described in the present invention refers to a polybutylene terephthalate resin obtained by condensing a dicarboxylic acid component containing at least terephthalic acid or an ester-forming derivative thereof (for example, an alkyl ester of C1-C6, an acyl halide, etc.) and a diol component containing at least an alkylene glycol having 4 carbon atoms (for example, 1,4-butanediol) or an ester-forming derivative thereof (for example, an acetylated product, etc.).
[0033] Preferably, the molar content of butylene terephthalate units in the copolymer containing butylene terephthalate units is ≥ 60%, for example, it can be 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, etc.
[0034] Preferably, the polyethylene terephthalate is obtained by the polycondensation of diacid units with ethylene glycol.
[0035] Preferably, the ethylene glycol is of bio-origin.
[0036] Preferably, the biological source is mainly crop straw such as corn, sugarcane or wheat.
[0037] Preferably, the diacid unit comprises any one of terephthalic acid, dimethyl terephthalate and optional aromatic carboxylic acid ester derivatives, optional aliphatic polyesters, and optional alicyclic dicarboxylic acid esters, or a combination of at least two thereof.
[0038] Preferably, the aromatic carboxylic acid ester derivatives include any one of dimethyl isophthalate, dimethyl isophthalate-5-sulfonate, dimethyl phthalate, dimethyl methyl terephthalate, dimethyl naphthalate or dimethyl biphenyl dicarboxylate, or a combination of at least two thereof.
[0039] Preferably, the aliphatic polyester includes any one of dimethyl adipate, dimethyl pimelate, dimethyl suberate, dimethyl azelate or dimethyl dodecanedicarboxylate, or a combination of at least two thereof.
[0040] Preferably, the alicyclic dicarboxylic acid ester includes any one of dimethyl cyclohexanedicarboxylate, dimethyl hexahydroisophthalate or dimethyl hexahydrophthalate, or a combination of at least two thereof.
[0041] Preferably, the brominated flame retardant includes any one of tetrabromobisphenol A, bromotriazine, brominated epoxy, decabromodiphenylethane, decabromodiphenyl ether, brominated polyimide, brominated polystyrene, polybrominated styrene, brominated polycarbonate or brominated polyacrylate, or a combination of at least two thereof.
[0042] Preferably, the synergistic flame retardant comprises an antimony-containing compound.
[0043] Preferably, the antimony-containing compound includes any one of antimony trioxide, sodium antimonate or antimony pentoxide, or a combination of at least two thereof.
[0044] Preferably, the weight average molecular weight of the polysulfone is ≥5000 g / mol, for example, it can be 5500 g / mol, 6000 g / mol, 6500 g / mol, 7000 g / mol, 8000 g / mol, 9000 g / mol, 10000 g / mol, 12000 g / mol, 15000 g / mol, 20000 g / mol, 30000 g / mol or 50000 g / mol, etc.
[0045] Preferably, the polysulfone includes any one of bisphenol A type polysulfone (PSU), polyphenylene sulfone resin (PPSU) or polyether sulfone resin (PESU) or a combination of at least two thereof, and more preferably polyphenylene sulfone resin.
[0046] Preferably, the average particle size of the talc is ≤10 μm, for example, it may be 10 μm, 9 μm, 8 μm, 7.5 μm, 7 μm, 6 μm, 5 μm, 4 μm, 3 μm, 2 μm, 1 μm or 0.5 μm, and more preferably ≤8 μm.
[0047] As a preferred technical solution of the present invention, talcum powder with a specific particle size range is used to enable it to be better dispersed in polyester, thereby improving the impact strength of the material while synergistically improving the flame retardant efficiency with polysulfone.
[0048] The particle size in the present invention is measured according to Stokes' law using an automatic X-ray sedimentation particle size analyzer, SediGraph III5120.
[0049] Preferably, the reinforcement material comprises glass fibres.
[0050] Preferably, the polyester composition further comprises 0.1-1 parts by weight of a color stabilizer, for example, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight or 0.8 parts by weight.
[0051] Preferably, the color stabilizer includes any one of a phosphite stabilizer, a phosphonite stabilizer, a hindered phenol stabilizer or an amide stabilizer, or a combination of at least two thereof.
[0052] Preferably, the amide stabilizer includes any one of o-aminobenzamide, 1,8-diaminonaphthalene, allantoin or N,N'-1,6-hexanediylbis(2-amino-benzamide) or a combination of at least two thereof.
[0053] In a second aspect, the present invention provides a method for preparing the polyester composition as described in the first aspect, the preparation method comprising the following steps:
[0054] The polyester resin, the brominated flame retardant, the synergistic flame retardant, the polysulfone, the talc powder, the optional reinforcing material and the optional color stabilizer are uniformly mixed, and the mixture is extruded and granulated to obtain the polyester composition.
[0055] Preferably, the extrusion granulation is carried out in a twin-screw extruder.
[0056] Preferably, the temperature of the extrusion granulation is 30-260°C, for example, 40°C, 60°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C or 250°C.
[0057] Preferably, the temperature of the first zone of the twin-screw extruder is 30-200°C, the temperature of the second zone is 220-260°C, the temperature of the third zone is 220-260°C, the temperature of the fourth zone is 200-240°C, the temperature of the fifth zone is 170-240°C, the temperature of the sixth zone is 170-230°C, the temperature of the seventh zone is 170-230°C, the temperature of the eighth zone is 170-230°C, the temperature of the ninth zone is 170-240°C, and the head temperature is 210-25 0℃, the extrusion time is 1-3min (for example, it can be 1.2min, 1.5min, 1.8min, 2min, 2.2min, 2.5min or 2.8min, etc.), the main engine speed is 300-500 rpm (for example, it can be 320 rpm, 350 rpm, 380 rpm, 400 rpm, 420 rpm, 450 rpm or 480 rpm, etc.).
[0058] In a third aspect, the present invention provides a use of the polyester composition as described in the first aspect in automobiles, electronic appliances or household appliances.
[0059] Compared with the prior art, the present invention has at least the following beneficial effects:
[0060] The present invention provides a polyester composition, a preparation method and an application thereof. Polysulfone and talcum powder are introduced into a traditional bromine-based flame retardant polyester for compounding, and 0.8 mm V-0 flame retardancy can be achieved without adding fluorine-containing substances. In some preferred technical schemes, 0.4 mm ultra-thin V-0 flame retardancy can be achieved, thereby obtaining a polyester composition with excellent thin-wall flame retardant effect, and meeting the application requirements of green, environmentally friendly and efficient flame retardancy. DETAILED DESCRIPTION
[0061] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] In the following specific implementation of the present invention, the materials involved are as follows:
[0063] (1) Polyester resin
[0064] PET resin, PET BG80, Sinopec Yizheng Chemical Fiber Co., Ltd.;
[0065] PBT resin, PBT GX121, Sinopec Yizheng Chemical Fiber Co., Ltd.
[0066] (2) Brominated flame retardants
[0067] Brominated epoxy, F-2100, Israel Chemical Group.
[0068] (3) Polysulfone
[0069] PSU, P-1700NT 11, Solvay Specialty Polymers (Changshu) Co., Ltd.;
[0070] PPSU, KFSU12, Kingfa Science & Technology Co., Ltd.;
[0071] PESU, A-301NT, Solvay (Shanghai) Co., Ltd.
[0072] (4) Talc
[0073] Talc, CHX05L, Liaoning Aihai Yimi Mining Co., Ltd., average particle size 7.5 μm;
[0074] Talc, Ultra5L, Liaoning Aihaiyimi Mining Co., Ltd., average particle size 3.1 μm;
[0075] Talc, Finntalc M05SLC, produced in Mondo, Italy, with an average particle size of 9 μm.
[0076] (5) Other materials
[0077] Fiberglass, ECS11-4.5-534A, Jushi, China;
[0078] Color stabilizer, antioxidant 1010, Yingkou Fengguang Chemical Co., Ltd.;
[0079] Calcium carbonate, AC-MLT04, Dongguan Meilitai Chemical Co., Ltd.;
[0080] Polytetrafluoroethylene (PTFE), DF-102, Shandong Dongyue Shenzhou New Materials Co., Ltd.
[0081] Example 1
[0082] A polyester composition, comprising, by weight, 48.5 parts of PBT resin (PET BG80), 14 parts of brominated flame retardant F-2100, 3 parts of antimony trioxide, 3 parts of PPSU (KFSU12), 1 part of talc (Ultra5L), 30 parts of glass fiber, and 0.5 parts of antioxidant 1010;
[0083] The polyester composition is prepared by the following method:
[0084] After uniformly mixing the components, the components are melt-extruded and granulated by a twin-screw extruder to obtain the polyester composition;
[0085] The temperature of zone 1 of the twin-screw extruder is 50°C, the temperature of zone 2 is 220°C, the temperature of zone 3 is 230°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 230°C, the temperature of zone 6 is 200°C, the temperature of zone 7 is 180°C, the temperature of zone 8 is 180°C, the temperature of zone 9 is 190°C, the head temperature is 230°C, the extrusion time is 2min, and the main engine speed is 400 rpm.
[0086] The polyester composition provided in Example 1 was subjected to the following performance tests:
[0087] (1) Vertical combustion
[0088] The vertical burning properties of the polyester composition were tested according to the UL94 vertical burning test method.
[0089] (2) Izod notched impact strength
[0090] The notched Izod impact strength of the polyester compositions was tested according to ISO 180:2023.
[0091] (3) Fluorine content
[0092] The fluorine content of the polyester composition was tested according to EN14582:2016.
[0093] The test results are summarized in Table 1.
[0094] Examples 2-8, Comparative Examples 1-3
[0095] A polyester composition, which differs from Example 1 in that the formula of the polyester composition is different, as shown in Table 1; wherein the dosage unit of each component is "parts by weight" of solid content; the preparation method and performance testing method of the polyester composition are the same as those of Example 1.
[0096] Table 1
[0097]
[0098] Table 2
[0099]
[0100] The test results show that the present invention can achieve 0.8mm V-0 flame retardancy and 0.4mm ultra-thin V-0 flame retardancy or V-1 flame retardancy by introducing polysulfone and talcum powder into the traditional brominated flame retardant polyester system for compounding without adding PFAS substances. At the same time, the cantilever beam notched impact strength is ≥7kJ / cm 2 , specifically 7-9 kJ / cm 2 , fluorine content ≤25ppm, and a high-strength polyester composition with green environmental protection and high efficiency flame retardancy is obtained. It can be seen from Examples 1-15 of the present invention that the present invention further improves the combined performance of the polyester composition by using PPSU as the polysulfone component, the particle size of talcum powder is within a specific range, and a specific ratio of polyester and talcum powder is used, while optimizing the specific amount of each component. It can achieve 0.8mm V-0 flame retardancy without adding PFAS substances, and can achieve 0.4mm ultra-thin V-0 flame retardancy, and the cantilever beam notched impact strength is ≥7.8kJ / cm 2 , specifically 7.8-9kJ / cm 2 , fluorine content ≤25ppm. Specifically:
[0101] By comparing Example 1 with Examples 3 and 4, it can be seen that the present invention can achieve better flame retardant effect and improve the notched Izod impact strength of the polyester composition by further using PPSU as the polysulfone component.
[0102] By comparing Example 1 with Examples 5 and 6, it can be seen that when the particle size of the talc powder used is too large, the system compatibility is poor and the dispersion is uneven, resulting in decreased flame retardancy of the obtained polyester composition and lower Izod notched impact strength.
[0103] By comparing Example 1 with Examples 7-10, it can be seen that the flame retardant effect of the polyester composition is further improved by using a specific ratio of polyester and talcum powder in the present invention, while the mechanical strength of the material is increased, so that it has better application performance.
[0104] By comparing Example 1 with Examples 11-15, it can be seen that the present invention further improves the flame retardant effect of the polyester composition by further optimizing the amount of each component in the polyester composition, and at the same time improves the mechanical strength of the material, so that it has better application performance. By comparing Example 1 with Comparative Examples 1, 2, and Comparative Example 4, it can be seen that the present invention improves the flame retardant effect of the system by introducing a combination of polyester and talcum powder into the bromine-based flame retardant system polyester, so that it can achieve ultra-thin flame retardancy while having excellent mechanical properties. When the lack of polysulfone and talcum powder or the replacement of talcum powder with other inorganic particles is not adopted, the flame retardant performance of the obtained polyester composition is poor, and it is difficult to meet the application requirements of thin-wall flame retardancy.
[0105] By comparing Example 1 with Comparative Example 3, it can be seen that the present invention does not need to add PTFE to inhibit the dripping of the ultra-thin flame-retardant polyester material during combustion, and still achieves excellent thin-wall flame retardant effect, avoids the use of fluorine-containing substances, and eliminates people's concerns about the use of PFAS in materials. The applicant declares that the above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyester composition, characterized in that In parts by weight, the polyester composition comprises 40-60 parts of polyester resin, 5-20 parts of brominated flame retardant, 0.5-5 parts of synergistic flame retardant, 0.1-15 parts of polysulfone, 0.05-5 parts of talc, and 15-40 parts of reinforcing material; The polyester composition does not include PFAS substances.
2. The polyester composition according to claim 1, characterized in that In parts by weight, the polyester composition comprises 45-55 parts of polyester resin, 8-15 parts of brominated flame retardant, 1-4 parts of synergistic flame retardant, 0.5-5 parts of polysulfone, 0.3-3 parts of talc, and 15-40 parts of reinforcing material; Preferably, the mass ratio of the polysulfone to talc is (1-10):
1.
3. The polyester composition according to claim 1, characterized in that The polyester resin includes polybutylene terephthalate resin and / or polyethylene terephthalate.
4. The polyester composition according to claim 1, characterized in that The brominated flame retardant includes any one of tetrabromobisphenol A, bromotriazine, brominated epoxy, decabromodiphenylethane, decabromodiphenyl ether, brominated polyimide, brominated polystyrene, polybrominated styrene, brominated polycarbonate or brominated polyacrylate, or a combination of at least two thereof.
5. The polyester composition according to claim 1, characterized in that The synergistic flame retardant includes an antimony-containing compound; Preferably, the antimony-containing compound includes any one of antimony trioxide, sodium antimonate or antimony pentoxide, or a combination of at least two thereof.
6. The polyester composition according to claim 1, characterized in that The polysulfone includes any one of bisphenol A type polysulfone, polyphenylene sulfone resin or polyether sulfone resin or a combination of at least two thereof.
7. The polyester composition according to claim 1, characterized in that The average particle size of the talc powder is ≤10 μm, preferably ≤8 μm.
8. The polyester composition according to claim 1, characterized in that The reinforcing material includes glass fiber; Preferably, the polyester composition further comprises 0.1-1 parts by weight of a color stabilizer; Preferably, the color stabilizer comprises any one or a combination of at least two of a phosphite stabilizer, a phosphonite stabilizer, a hindered phenol stabilizer or an amide stabilizer; Preferably, the amide stabilizer includes any one of o-aminobenzamide, 1,8-diaminonaphthalene, allantoin or N,N'-1,6-hexanediylbis(2-amino-benzamide) or a combination of at least two thereof.
9. A method for preparing a polyester composition according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The polyester resin, the brominated flame retardant, the synergistic flame retardant, the polysulfone, the talc powder, the optional reinforcing material, and the optional color stabilizer are uniformly mixed, and the mixture is extruded and granulated to obtain the polyester composition; Preferably, the extrusion granulation is carried out in a twin-screw extruder; Preferably, the temperature of the extrusion granulation is 30-260°C.
10. Use of the polyester composition according to any one of claims 1 to 8 in automobiles, electronic appliances or household appliances.
Citation Information
Patent Citations
High-performance PET / PBT material for junction box of air conditioner compressor and preparation method of high-performance PET / PBT material
CN113248881A
Fire resistance polybutylece terephthalate resin composition
CN101613520A
Flame-retardant polybutylene terephthalate resin composition
CN114174426A
Polyester resin composition
JP2011178975A
Cited By
Flame-retardant polyester composite material as well as preparation method and application thereof
CN120535925A
Flame-retardant polyester composite material and preparation method and application thereof
CN120535925B